Mushrooms as Potential Sources of Active Metabolites and Medicines - Bhambri, Anne; Srivastava, Malay; Mahale, Vivek G.; Mahale, Sushma; Karn, Santosh Kumar (Frontiers in Microbiology, 2022)
Background Mushrooms exist as an integral and vital component of the ecosystem and are very precious fungi. Mushrooms have been traditionally used in herbal medicines for many centuries. Scope and Approach There are a variety of medicinal mushrooms mentioned in the current work such as Agaricus, Amanita, Calocybe, Cantharellus, Cordyceps, Coprinus, Cortinarius, Ganoderma, Grifola, Huitlacoche, Hydnum, Lentinus, Morchella, Pleurotus, Rigidoporus, Tremella, Trametes sp., etc., which play a vital role in various diseases because of several metabolic components and nutritional values. Medicinal mushrooms can be identified morphologically on the basis of their size, color (white, black, yellow, brown, cream, pink and purple-brown, etc.), chemical reactions, consistency of the stalk and cap, mode of attachment of the gills to the stalk, and spore color and mass, and further identified at a molecular level by Internal Transcribed Spacer (ITS) regions of gene sequencing. There are also other methods that have recently begun to be used for the identification of mushrooms such as high-pressure liquid chromatography (HPLC), nuclear magnetic resonance spectroscopy (NMR), microscopy, thin-layer chromatography (TLC), DNA sequencing, gas chromatography-mass spectrometry (GC-MS), chemical finger printing, ultra-performance liquid chromatography (UPLC), fourier transform infrared spectroscopy (FTIR), liquid chromatography quadrupole time-of-flight mass spectrometry (LCMS-TOF) and high-performance thin-layer chromatography (HPTLC). Lately, the matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) technique is also used for the identification of fungi. Key Finding and Conclusion Medicinal mushrooms possess various biological activities like anti-oxidant, anti-cancer, anti-inflammatory, anti-aging, anti-tumor, anti-viral, anti-parasitic, anti-microbial, hepatoprotective, anti-HIV, anti-diabetic, and many others that will be mentioned in this article. This manuscript will provide future direction, action mechanisms, applications, and the recent collective information of medicinal mushrooms. In addition to many unknown metabolites and patented active metabolites are also included.